Microalgal biofuels: Challenges and prospective in the framework of circular bioeconomy - Sajani Piyatilleke; Bavatharny Thevarajah; P.H.V. Nimarshana; Thilini U. Ariyadasa (Energy Nexus)
Microalgae are a promising bioresource, facilitating carbon dioxide sequestration and wastewater bioremediation whilst synthesizing lipids and carbohydrates that could be processed into biofuels such as biodiesel, biochar, biogas, and biohydrogen. Microalgae has the potential to play a major role within a sustainable bioeconomy, through zero-waste, carbon-neutral production of multiple biofuels by valorizing the entire biomass. Despite the multitude of advantages in deriving biofuels from microalgae, techno-economic challenges, such as chemical requirements for cultivation, energy requirements of harvesting, and tradeoffs between efficiency-energy-cost of downstream processing methods act as a barrier to scale-up and economically viable operation under the framework of a circular bioeconomy. Thus, this review aims to discuss the potential of microalgae-derived biofuels in achieving a circular bioeconomy through perspectives of possible integration with wastewater bioremediation as well as multiproduct biorefining operations. Furthermore, the review will detail the encompassing techno-economic and sustainability challenges toward large-scale implementation of microalgal biofuels within the framework of a circular bioeconomy, while assessing the potential solutions and perspectives.